Enantioselective construction of silicon-stereogenic vinylsilanes from simple alkenes - Kailin Yin; Jinyu Zhang; Deng Pan; Shu-Han Chen; Song Chen; Yufeng Shi; Genping Huang; Dongbing Zhao (Nature Communications)
Abstract The diverse utility of acyclic vinylsilanes has driven the interest in the synthesis of enantioenriched vinylsilanes bearing a Si-stereogenic center. However, the predominant approaches for catalytic asymmetric generation of Si-stereogenic vinylsilanes have mainly relied on transition metal-catalyzed reactions of alkynes with different silicon sources. Here we successfully realize the enantioselective synthesis of linear silicon-stereogenic vinylsilanes with good yields and enantiomeric ratios from simple alkenes under rhodium catalysis. The significance of this transformation lies in its ability to achieve regioconvergent and enantioconvergent conversion, efficiently transforming petroleum-derived isomeric mixtures of olefin feedstocks into a single regio- and stereoisomer product. The practicality of this method is further exemplified by the diverse downstream transformations of these enantioenriched silicon-stereogenic vinylsilanes leveraging the olefin functionality and the leaving group nature of the aryl substituent on silicon as well as the development of chiral π-conjugated double bond systems.